Laparoscopic excision of a retroperitoneal schwannoma: A case report. Issue 2 (28th May 2018) - Ohsawa, Manato; Miguchi, Masashi; Yoshimitsu, Masanori; Oishi, Koichi; Kohashi, Toshihiko; Hihara, Jun; Mukaida, Hidenori; Kaneko, Mayumi; Egi, Hiroyuki; Ohdan, Hideki; Hirabayashi, Naoki
Abstract: Schwannomas are tumors originating from the Schwann cells of the peripheral nerve sheath. Only 1%–3% of schwannomas reportedly occur in the pelvis. In a 67‐year‐old man, a pelvic mass that was 52 mm in diameter was incidentally diagnosed during a preoperative CT evaluation for prostate cancer. Preoperative 3‐D reconstruction CT showed that the feeding artery to the tumor originated from the internal iliac artery and the drainage vein from the internal iliac vein. Each vessel could be isolated, clipped, and cut with minimal bleeding. The tumor was easily dissected from adjacent structures and was completely resected via laparoscopic surgery. Histopathology and immunohistochemistry of the excised specimen revealed a benign schwannoma. Using 3‐D reconstruction to recognize a tumor's positional relation with the supplying vessels is important for avoiding complications during laparoscopic resection in the narrow pelvis. Laparoscopic resection is safe, feasible, and effective for retroperitoneal schwannoma.